Sustainability Orientation and Sustainable Entrepreneurship Intention: The Mediating Role of Entrepreneurial Opportunity Recognition - Bapoo, Mivesh Ashwyn; Tehseen, Shehnaz*; Syed Arslan Haider,; Mohar Yusof,; Motaghi, Hamed (Allied Business Academies, 2022)
The purpose of this research is twofold. First, to examine the influence of four dimensions of sustainability orientation which are sustainability knowledge, sustainability culture, sustainability practices and commitment to environmental sustainability on the sustainable entrepreneurship intention of business schools’ students in Malaysia; and the second is to explore the mediating role of entrepreneurial opportunity recognition among these variables. The data for this study were collected from business school students in Malaysia through a standard self-administered online structured questionnaire. The data were analyzed through the PLS-SEM approach. The findings have revealed the direct effect of commitment to environmental sustainability on sustainable entrepreneurship intention. However, sustainability culture, sustainability knowledge and sustainability practices have been found to have no significant direct effect on sustainable entrepreneurship intention. Entrepreneurial opportunity recognition has successfully mediated the relationship between sustainability culture and commitment to environmental sustainability with sustainable entrepreneurship intention. Nonetheless, it has failed to mediate the relationship between sustainability knowledge and sustainability practices with sustainable entrepreneurship intention. The existence of the mediation of entrepreneurial opportunity recognition between sustainability culture and commitment to environmental sustainability with sustainable entrepreneurship intention has contributed knowledge to the sustainable entrepreneurship and sustainability orientation literature.